Quality Assessors' Feedback and Recommendations on Music Education in Hong Kong Kindergartens - Yan Lam Ho; Alfredo Bautista (MDPI AG, 2024)
In Hong Kong, quality assessors from the Education Bureau (EDB) visit kindergartens to conduct Quality Review (QR) assessments. Their written reports, therefore, reflect the official local perspective of quality kindergarten education. We conducted a content analysis of 323 QR reports focusing on the positive and negative feedback and recommendations for improvement regarding music education. Two coding schemes were developed using an inductive approach. High inter-reliability was obtained. The most frequently mentioned positive feedback codes were related to sufficient exposure to music and enjoyable musical learning experiences. In contrast, there were negative feedback codes pointing out that children's musical exposure was insufficient at Kindergarten 3 (children aged 5-6 years), and some musical activities were poorly prepared and/or designed. Children's music learning outcomes were rarely mentioned in the reports. The analyses indicate that the local understanding of kindergarten music education strongly emphasizes exposing children to enjoyable musical activities, with a lower focus on the nature and quality of musical learning. We conclude that the QR reports reflect a teacher-centric view of music education. Findings may inform curriculum designers and teacher educators about EDB's expectations in the area of music education. Future research should explore the perspectives of other kindergarten stakeholders such as teachers, principals, and teacher educators.